FIRST-TIME AUTHOR IN THE LITHUANIAN BOOK MARKET - GRINIŪTĖ, ILONA (Knygotyra, 2010)
The object of the article is the publishing of first-time authors’ books in Lithuania. The aim of the work was to explore the situation of first-time authors in the Lithuanian book market in 1990–2009 and to reveal its main problems. The tasks of the work were to define the conception of first-time author, to explore his role and its changes in the Lithuanian publishing market, to determine the ways of selecting of first-time literature books, to study the features of first-time book publishing and marketing, and to reveal the problems the publishers face in Lithuania. Analysis of literature sources and interviews has shown that first-time authors are essential for the publishers as professional writers. Furthermore, it has been discovered that there is a great demand of first-time books in the market. However, it has encouraged the development of graphomania, i.e. the writing of literarily worthless books. For this particular reason, it is important to distinguish between professional and talented first-time authors and graphomaniac writers. Besides, the work shows that the present situation of first-time book publishing is extremely related to a strong competition among the writers and to competition for publishing houses and readers. As a result, the literature is getting more and more dependent on the reader’s influence. On the one hand, such literature creates a higher level of trust between the writer and his reader; on the other hand, it strengthens the commercial side of first-time book publishing. First-time books are being produced by the bigger number of Lithuanian publishing houses. The majority of publishers produce individual first-time books while the others publish series of such books which require more effort and time constraint. Also, such books are being published by both large and small publishing companies, and the financial risk is partly transferred to national or private institutions. In addition, it has been noticed that publishers do not attempt to find or pull new authors and do not use the wide possibilities of literature festivals and contests. The research of a specific case has revealed the fact that it is not necessary to promote big advertising campaigns or use extraordinary marketing actions and money to successfully publish a first-time book. Most important are a close cooperation between the author and his publisher during the whole publishing process and, of course, a professionally written book.